2010
DOI: 10.2478/v10014-010-0004-2
|View full text |Cite
|
Sign up to set email alerts
|

Selenium induced lower respiratory potential in Glycine max (L.) Merr

Abstract: Effect of selenium (Se) was studied in soybean (Glycine max (L.) Merr.) cv. Olna in Ljubljana, Slovenia. Se was added to plants as foliary spraying. Quantum yield of photosystem II (PSII) and respiratory potential measured as ETS activity of mitochondria were measured two times in the growing season. Respiratory potential was higher in young plants compared to mature plants. Se induced the lowering of respiratory potential. Addition of Se had no effect on quantum yield of photosystem II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The potential quantum yield and effective quantum yield of PSII were unaffected by Se treatment (Table 1). Similar results were obtained for Cucurbita pepo , chicory (Germ et al, 2007b), Eruca sativa , tartary buckwheat (Breznik et al, 2005), soybean (Mechora and Germ, 2010), and Hordeum vulgare (Valkama et al, 2003) (Table 2). Values of F v /F m were close to the theoretical maximum of 0.83 (Schreiber et al, 1995), which indicates reversible inactivation rather Results are expressed as means ± SD of six plants.…”
Section: Resultssupporting
confidence: 90%
“…The potential quantum yield and effective quantum yield of PSII were unaffected by Se treatment (Table 1). Similar results were obtained for Cucurbita pepo , chicory (Germ et al, 2007b), Eruca sativa , tartary buckwheat (Breznik et al, 2005), soybean (Mechora and Germ, 2010), and Hordeum vulgare (Valkama et al, 2003) (Table 2). Values of F v /F m were close to the theoretical maximum of 0.83 (Schreiber et al, 1995), which indicates reversible inactivation rather Results are expressed as means ± SD of six plants.…”
Section: Resultssupporting
confidence: 90%
“…Selenium induced decrease in mitochondrial activities were observed in leaves along with Se accumulation. The decrease in ETS activity indicated higher Se‐induced stress to plants as a result the plants cannot cope and therefore respiratory potential drops . The lower photosynthetic efficiency along with lower ETS activity indicated that Se negatively affected the respiratory chain as well as photosynthetic processes.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in ETS activity indicated higher Se-induced stress to plants as a result the plants cannot cope and therefore respiratory potential drops. 8 The lower photosynthetic efficiency along with lower ETS activity indicated that Se negatively affected the respiratory chain as well as photosynthetic processes. This might be due to the reason that clusters of iron-sulfur proteins of these organelles can be substituted by iron-Se clusters that are larger in size and do not fit into apoproteins.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
See 2 more Smart Citations